p38 MAPK Activation Promotes Denervated Schwann Cell Phenotype and Functions as a Negative Regulator of Schwann Cell Differentiation and Myelination - Yang, David P. (Society for Neuroscience, 2012)
Physical damage to the peripheral nerves triggers Schwann cell injury response in the distal nerves in an event termed Wallerian degeneration: the Schwann cells degrade their myelin sheaths and dedifferentiate, reverting to a phenotype that supports axon regeneration and nerve repair. The molecular mechanisms regulating Schwann cell plasticity in the PNS remain to be elucidated. Using both in vivo and in vitro models for peripheral nerve injury, here we show that inhibition of p38 mitogen-activated protein kinase (MAPK) activity in mice blocks Schwann cell demyelination and dedifferentiation following nerve injury, suggesting that the kinase mediates the injury signal that triggers distal Schwann cell injury response. In myelinating cocultures, p38 MAPK also mediates myelin breakdown induced by Schwann cell growth factors, such as neuregulin and FGF-2. Furthermore, ectopic activation of p38 MAPK is sufficient to induce myelin breakdown and drives differentiated Schwann cells to acquire phenotypic features of immature Schwann cells. We also show that p38 MAPK concomitantly functions as a negative regulator of Schwann cell differentiation: enforced p38 MAPK activation blocks cAMP-induced expression of Krox 20 and myelin proteins, but induces expression of c-Jun. As expected of its role as a negative signal for myelination, inhibition of p38 MAPK in cocultures promotes myelin formation by increasing the number as well as the length of individual myelin segments. Altogether, our data identify p38 MAPK as an important regulator of Schwann cell plasticity and differentiation.